Una aproximación a la reconstrucción de la historia poblacional del Nordeste argentino desde el estudio de los linajes uniparentales - Rodríguez Golpe, Daniela Carmen (2022)
Northeast Argentina is characterized by the presence of ethnic, cultural and linguistic diversity; and by a history of population movements linked to geopolitical variations. The aim of this paper is to present a research design, structured in three analytical axes (local, regional and South American), to explore the population history of the region through the characterization of maternal and paternal lineages of the cities of Corrientes (CRR N=151) and Formosa (FOR N=274). Analysis techniques and methods were detailed, the research questions addressed in each axis were outlined and the results of the first axis were presented. Genetic contributions of Native American, western Eurasia, and sub-Saharan Africa origin were estimated. Majority frequencies of Native American lineages were obtained through the maternal line (FOR=85%, CRR=89,4%). The Eurasian (FOR=9,93%, CRR=12,41%) and African (FOR=2,55%, CRR=0,66%) lineages were also present. On the other hand, more than 80% of the paternal lineages were of Eurasian origin, with 55% corresponding to R1 (FOR=55,2%, CRR=54,7%). The native American fraction (FOR= 4,9%; CRR=3,2%), provided the lowest frequencies documented for Argentina. Molecular data were compared with genealogical data and contextualized with historical evidence.